2016
DOI: 10.1175/jcli-d-14-00834.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal Variation of the Strength of the East Asian Trough and Its Climatic Impacts in Boreal Winter

Abstract: The East Asian trough (EAT) is a distinct component of the boreal winter circulation whose strength corresponds to the amplitude of the Northern Hemispheric stationary waves. In this study, the mechanism and climatic impacts of the intraseasonal variations of the EAT’s strength are investigated through composite analysis and dynamical diagnostics. The significant roles played by the low-frequency Rossby wave (RW) and synoptic transient eddy (TE) are revealed. Before the peaks of strong EAT events, an upper-tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 51 publications
11
123
0
Order By: Relevance
“…A connection of positive height anomalies with those in the Arctic region is obvious in phases 6–7 (Figures f and g). Negative height anomalies over East Asia denote a deepened East Asian trough, which, together with a strengthened surface Siberia high (Figure h) and anomalous lower level northerly wind anomalies (Figure h), provide favorable condition for occurrence of cold anomalies in eastern China (Song et al, ; Song & Wu, ). The weakening/deepening of the East Asian trough and the weakening/strengthening of the Siberian high are related to the Rossby wave activity.…”
Section: Comparison Of Atmospheric Circulation Anomalies Between Posimentioning
confidence: 99%
“…A connection of positive height anomalies with those in the Arctic region is obvious in phases 6–7 (Figures f and g). Negative height anomalies over East Asia denote a deepened East Asian trough, which, together with a strengthened surface Siberia high (Figure h) and anomalous lower level northerly wind anomalies (Figure h), provide favorable condition for occurrence of cold anomalies in eastern China (Song et al, ; Song & Wu, ). The weakening/deepening of the East Asian trough and the weakening/strengthening of the Siberian high are related to the Rossby wave activity.…”
Section: Comparison Of Atmospheric Circulation Anomalies Between Posimentioning
confidence: 99%
“…According to the research of Song et al . [], an accumulation of the wave energy from upstream incoming waves can affect the EAT directly. On the other hand, upstream waves interact with surface air temperature anomalies and lead to upward wave propagation converging toward the EAT, contributing to the EAT indirectly.…”
Section: The Relationship Between the December Nao And The Following mentioning
confidence: 99%
“…This cyclone appears as a merge of the two wave trains. Previous studies have identified the effects on the cold events over East Asia of either the north wave train (Bueh et al, ; Hsu, ; Hsu & Wallace, ; Joung & Hitchman, ; Lau & Lau, ; Park et al, ; Song et al, ; Suda, ; Takaya & Nakamura, , , ; Wu & Chan, ; Yang & Li, ; Yao et al, ) or the south wave train (Song & Wu, ; Wen et al, ). Here, we detect that the two wave trains may coexist in association with intraseasonal variability of the East Asian winter monsoon.…”
Section: Two Wave Trains Associated With the East Asian Intraseasonalmentioning
confidence: 99%
“…Some studies detected a wave train over the subtropics in the upper troposphere (Branstator, ; Li & Sun, ; Li & Zhou, ; Song et al, ; Song & Wu, ; Watanabe, ; Wen et al, ). The subtropical wave train begins from the North Atlantic and the Mediterranean regions and propagates to East Asia along the subtropical jet stream (Hu et al, ; Song et al, ; Watanabe, ).…”
Section: Introductionmentioning
confidence: 99%